An integrative description of Diploechiniscus oihonnae (Richters, 1903) population from near the original type locality in Merok (Norway) - Kaczmarek, Łukasz; Kayastha, Pushpalata; Gawlak, Magdalena; Mioduchowska, Monika; Roszkowska, Milena (Zootaxa, 2021)
In the present study, we used integrative taxonomy to describe a population of Diploechiniscus oihonnae (Richters, 1903) from the neotype locality in Merok (Norway). We found no differences in the chaetotaxy formula between the life stages and sex of Dpl. oihonnae. The presence of filaments at Bd in some specimens of Dpl. oihonnae appears to be random and most likely represents the morphological variability of this species. We also obtained DNA sequences of 18S rRNA, 28S rRNA, ITS-2, and COI of Dpl. oihonnae from the neotype locality for comparison with the sequences available in GenBank, which showed low genetic differences between the neotypic population and specimens from other localities. Therefore, we decided to establish our specimens from Merok as neotype and neoparatypes of Dpl. oihonnae. Additionally, based on morphological characters, Dpl. horningi (Schuster & Grigarick, 1971) was synonymised with Dpl. oihonnae.